KEPRIBADIAN TOKOH AKU DALAM CERPEN HITOFUSA NO BUDOU KARYA ARISHIMA TAKEO - Adityo, Hanif Febrian; Mulyadi, Budi; Fadli, Zaki Ainul (Japanese Literature, 2016)
Hitofusa No Budou is a short story by Arishima Takeo. Hitofusa No Budou tells about an indigenous boy who lives and study in a foreign place. This research tries to reveal personality of the main character in the Hitofusa No Budou. The methods is to obtain data with literatures. This research using a structural methods with uncovering the elements of literature that build up the whole meaning. Besides using structural methods, this research also using the approach literature psychoanalysis. Sigmund Freud's theory is used in this research. The result is that the main character has a personality, such as; envy, frightened or coward, uncommunicative, individually, justifies everything, whiny, unyielding, want to be a better individual, loner, obedient, can learning from experience and has a strong personality. The main character's personality structure is dominated by superego.